2017
DOI: 10.3233/jad-170567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise on Alzheimer’s Disease Biomarkers: A Systematic Review of Intervention Studies

Abstract: Physical exercise may be an important adjunct to pharmacological treatment of Alzheimer's disease (AD). Animal studies indicate that exercise may be disease modifying through several mechanisms including reduction of AD pathology. We carried out a systematic review of intervention studies of physical exercise with hippocampal volume (on MRI), amyloid-β, total tau, phosphorylated tau in cerebrospinal fluid (CSF), 18F-FDG-PET or amyloid PET as outcome measures in healthy subjects, patients with subjective memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 52 publications
4
40
0
3
Order By: Relevance
“…Currently, there are no disease-modifying drugs available for Alzheimer's disease and available pharmacological and supportive therapy are aimed at slowing disease progression. Clinical studies suggest physical exercise improves cognitive function and reduces the risk of developing AD [20]. The majority of the relevant studies are focused on the benefits of aerobic exercise, with only relatively few studies addressing whether resistance exercise, especially on a short-term basis, can improve learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no disease-modifying drugs available for Alzheimer's disease and available pharmacological and supportive therapy are aimed at slowing disease progression. Clinical studies suggest physical exercise improves cognitive function and reduces the risk of developing AD [20]. The majority of the relevant studies are focused on the benefits of aerobic exercise, with only relatively few studies addressing whether resistance exercise, especially on a short-term basis, can improve learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Delaying the onset of this failure might delay the onset of Alzheimer's disease. At present, physical exercise that maintains vascular health is one of the few potential protective treatments available for LOAD [55][56][57][58]. Indeed, a recent systematic review has revealed for the first time an association between physical exercise and better cognitive outcomes at expected symptom onset in individuals with fAD [59].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, exercise seems to reduce pathological changes, such as Ab deposition [10,11,13,14], tau pathology [15], and hippocampal atrophy [11,16] in animal models of AD. In humans, most of the studies have focused on exercise and hippocampal volume [17]. Results have been divergent, although most studies have shown a lack of association in both intervention [18][19][20][21][22] and observational studies [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%